Multiwalled carbon nanotube buckypaper induces cell cycle arrest and apoptosis in human leukemia cell lines through modulation of AKT and MAPK signaling pathways. Issue 7 (October 2015) - Dinicola, Simona; Masiello, Maria Grazia; Proietti, Sara; Coluccia, Pierpaolo; Fabrizi, Gianmarco; Palombo, Alessandro; Micciulla, Federico; Bistarelli, Silvia; Ricci, Giulia; Catizone, Angela; De Toma, Giorgio; Bizzarri, Mariano; et al.
Highlights BP decreased cell proliferation and increased apoptosis in leukemia cell lines. BP induced an arrest in G0/G1 phase of cell cycle with cyclin expression reduction. BP-mediated apoptosis was not mediated by ROS production. AKT and MAPK signaling pathways were involved in BP effects on leukemia cells.